Analysis of village development issues in regional online news media - Dwiyanto Indiahono (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2023)
The media and village development are two subjects that remain relevant and important to discuss. The article aimed to further examine village development issues in regional online news media. Suka (a fictitious name is adopted in this study to disguise the real name of the online news media), as a regional online news media, plays a strategic role in disseminating the regional government's agenda, helping monitor and evaluate regional policies, and providing information on the ideal village development measures. This study used a content analysis approach. The results of this study indicate that, in 2021, Suka reported seven news stories containing content with the keyword of village development. Those stories suggested four main issues of village development, namely sustainable village development, tourism village development, involvement of people with disabilities in village development, and the role of women and universities in village development. In these four main issues, a number of policy values in village development should be addressed by policymakers in formulating village development policies, namely integrated and sustainable development, utilization of local resources in development, along with increasing the role of the disabled people, women, and universities in village development.